Caenorhabditis elegans as a Model Host for Staphylococcus aureus Pathogenesis - Sifri, Costi D. (American Society for Microbiology, 2003)
Staphylococcus aureus, an important pathogen of humans and other warm-blooded animals, is also capable of killing the nematode Caenorhabditis elegans. Here, we show that C. elegans organisms that are fed S. aureus die over the course of several days in a process that is correlated with the accumulation of bacteria within the nematode digestive tract. Several S. aureus virulence determinants known or speculated to be important in mammalian pathogenesis, including the quorum-sensing global virulence regulatory system agr and the global virulence regulator sarA, the alternative sigma factor σ(B), alpha-hemolysin, and V8 serine protease, are required for full pathogenicity in nematodes. In addition, several defined C. elegans mutants were examined for susceptibility to S. aureus infection. Enhanced susceptibility to S. aureus killing was observed with loss-of-function mutations in the C. elegans genes esp-2/sek-1 and esp-8/nsy-1, which encode components of a conserved p38 MAP kinase signaling pathway involved in nematode defense against multiple pathogens. These results suggest that key aspects of S. aureus pathogenesis have been conserved, irrespective of the host, and that specific C. elegans host factors can alter susceptibility to this gram-positive human pathogen.